Godliness in a Golden Age: The Church and Wealth in Eighteenth-century Geneva - Kirk, Linda (Studies in church history, 1987)
In the eighteenth century two things about Geneva were clear to all observers: the city’s astonishing prosperity, and its Calvinism. It is not necessary to suppose that the second caused the first (although many contemporaries thought it did) to read in the republic and such conspicuous expatriates as Necker clear evidence that God rewarded hard work and virtuous living. All Europe knew of the scale and importance of the international Protestant banking connection to which Genevans contributed so much.